Estimated Model of Correlation Environmental Factor with Crowing Characteristics of Pelung Chickens - Asmara, Indrawati Yudha; Garnida, Dani; Hilmia, Nena; Maulana, Muhammad Irfan (Fakultas Peternakan, Universitas Padjadjaran, 2024)
Indonesia has high biodiversity, one of which is the diversity of local chickens such as Pelung chicken which is included in the singing chicken category. The characteristics of Pelung chicken's crowing sound are thought to be influenced by several factors, including genetic and environmental factors. This research was conducted to determine the relation of environmental factors to the characteristics of the crowing sound. The research was conducted using a survey method with purposive sampling techniques in Bandung, Cianjur and Sukabumi Regencies. The samples used were 32 Pelung chickens. The data observed were the duration, number, and crowing volume of Pelung chicken. When measuring sound characteristics, temperature, humidity, and light intensity were also measured. The data obtained were analyzed using multiple linear regression tests. The results of the research show that the regression equation for Duration and environment is Y=-0.547+0.142χ1+0.02χ2+0.066χ3, while crowing number with environment: Y=-47.48+1.17χ1+0.007χ2+0.423χ3, and Volume with environment: Y=62.563- 0.336χ1+0.01χ2+0.031χ3 with coefficients of determination (R2) of 0.179, 0.096, and 0.023 respectively. This research found that environmental factors such as temperature, light intensity, and humidity influenced the duration and number of Pelung chickens' crowing but did not influence the volume of the crowing sound. It is suspected that other factors and genetic factors are more dominant in influencing crowing characteristics.